Investigating the effects of a green economy transition on the electricity sector in the Western Cape province of South Africa: a system dynamics modelling approach - Oosthuizen, Juan (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.